Silicon-28-Tetrafluoride as an Educt of Isotope-Engineered Silicon Compounds and Bulk Materials for Quantum Systems - Owen C. Ernst; David Uebel; Roman Brendler; Konstantin Kraushaar; Max Steudel; Jörg Acker; Edwin Kroke (Molecules, 2024)
This review provides a summary of the existing literature on a crucial raw material for the production of isotopically pure semiconductors, which are essential for the development of second-generation quantum systems. Silicon-28-tetrafluoride (28SiF4) is used as an educt for several isotope-engineered chemicals, such as silane-28 (28SiH4) and silicon-28-trichloride (28SiHCl3), which are needed in the pursuit of various quantum technologies. We are exploring the entire chain from the synthesis of 28SiF4 to quantum applications. This includes the chemical properties of SiF4, isotopic enrichment, conversion to silanes, conversion to bulk 28Si and thin films, the physical properties of 28Si (spin neutrality, thermal conductivity, optical properties), and the applications in quantum computing, photonics, and quantum sensing techniques.